Nitric oxide increases Pb tolerance by lowering Pb uptake and translocation as well as phytohormonal changes in cowpea (Vigna unguiculata (L.) Walp.) - Sadeghipour, Omid (Penerbit Universiti Kebangsaan Malaysia, 2017)
Lead (Pb) is one of the most abundant toxic heavy metals which adversely affected growth and yield of crop plants. Nitric oxide (NO), an endogenous signaling molecule, has been suggested to be involved in defense responses to biotic and abiotic stresses in plants. The present study was done to induce Pb tolerance in cowpea plants by exogenous NO application using two levels of Pb, 0 and 200 mg Pb (NO3)2 kg-1 soil and three NO levels, 0, 0.5 and 1 mM sodium nitroprusside (SNP), as NO donor. The results showed that Pb treatment caused a significant increase in Pb concentration in all plant parts. Roots had higher levels of Pb than the stems, leaves and seeds. Furthermore, lead toxicity reduced auxin (IAA), cytokinin and gibberellic acid (GA3) content but increased abscisic acid (ABA) level. Moreover Pb stress decreased stomatal conductance, leaf area and consequently seed yield of cowpea. Exogenous application of NO at 0.5 mM noticeably alleviated the lead toxicity by improving the leaf area, stomatal conductance and seed yield. NO increased Pb tolerance by lowering Pb uptake and translocation, enhancing the promoting phytohormone (IAA, cytokinin and GA3) level and reducing ABA content.